Clean and Healthy Living Patterns, Balanced Nutrition, and Stress Management in The Covid-19 Pandemic (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Corona virus or COVID-19, the case started with pneumonia or a mysterious pneumonia in December 2019 in wuhan then spread throughout the world. At times like this, it is very important to try to increase the body's immunity by implementing the principles of a healthy lifestyle because the ability to survive this virus attack depends on the strength or weakness of immunity. Various important factors related to a person's immunity include diet, PHBS (Clean and Healthy Living Behavior), and no less important is stress management during a pandemic. Unfortunately, many people do not realize the importance of these factors in increasing immunity. Therefore, to increase public awareness, education is needed so that they can lead a more optimal healthy lifestyle. The target of the outreach activities that we carried out was to educate the community in Balai Kembang village, Mangkutana, East Luwu, South Sulawesi on November 17, 2019. The extension instruments used power point presentations and videos. Before and after the counseling, participants were given a knowledge questionnaire and the results were processed using SPSS Version 16. The extension went smoothly and had an impact on increasing community knowledge.